A comparison of three methodological approaches for meanline design of supercritical CO2 radial inflow turbines. (15th February 2020) - Lee, Sangkyoung; Gurgenci, Hal
Highlights: Comparative analysis of three meanline design models. Applicability of air turbine design method to supercritical CO2 radial turbines. Comparing supercritical CO2 turbine designs from three meanline design models. Optimal supercritical CO2 turbine designs covering a size range 0.3 MW–20 MW. Implications of relevant meanline design method selection for turbine designers. Abstract: Supercritical CO2 (s-CO2 ) Brayton power cycles are proposed as the next generation of thermal energy conversion due to their high efficiency and compactness. They are also scalable allowing construction of power plants at different sizes without efficiency costs. The radial inflow turbine is the critical component of small scale s-CO2 cycles. This paper presents a comparative analysis of three design methodologies that are commonly used in preliminary design of air turbines and discusses their applicability to s-CO2 turbines while proposing a process in which the turbine design can be incorporated into the higher-level thermodynamic cycle design and optimization by using these methods. The codes developed based on the three different design approaches are validated against experimental data. The twelve radial turbine designs (3 models × 4 turbine outputs) are generated and compared to furnish significant observations on implications of selecting the relevant meanline design methodology in designing s-CO2 radial turbines. Results show that methodologies suggested by Aungier and Moustapha et al. (Moustapha) produce similar blade geometries and flow features while Whitfield and Baines (W&B)'s model results in larger rotor blade heights and different flow characteristics. The rotor inlet radius is determined primarily by the operating condition, while the blade heights are determined by the design parameters. Turbine losses and performance predictions of different meanline models are also examined.